Advances in the field of stratigraphy and sedimentology in the Central American Journal of Geology - Aguilar, Teresita (2014)
The articles about sedimentary stratigraphy and sedimentology published over the 30 years of existence of ‘Revista Geológica de América Central’ showcase the importance that it has had in divulging advances in these disciplines, mainly in Costa Rica. 36 articles were analyzed, out of which, 22 were created by costaricans, 8 by scientists from other nationalities and costaricans working together, and 6 by scientists from other nationalities. From 1991 onwards the publishing of a series of geologic maps with the corresponding geologic and stratigraphic description